THE IMPACT OF FAST-FOOD CONSUMPTION ON HUMAN HEALTH - Abdulwahab, Mena M.; Mahmood, Yazen N. (Diyala Agricultural Sciences Journal, 2020)
In the last few years in Kurdistan in general and in Erbil especially many fastfood restaurant opening , and they sales are rise up every day with increased customer turnout to these kind of restaurant .All that affect in badly way on working in these kinds of restaurant from cleaning , serving ,safety , preparing the equipment for customer orders So, we depend the relationship between some diseases (Obesity , Diabetes , Heart disease , Blood pressure ) and fast-food consumption to measure how these factors (diseases) impacting with fast –food . We distribute 80 questioner and get 65 in different fast-food restaurant at family mallErbil. The results and findings of this research are analyzed by SPSS to build analysis and draw conclusion. The research findings showed distinctive relation between measuring factors.